Understanding Verse Meaning Among Students Through Mastery Learning Approach In Al-Qur'an Hadith Subject For Grade X At MA Hamasatul Muslimin Indonesia - Nurulhajj, Fadilah Arfan; Inayati, Fajriah; Sukmara, Ghina Fadlilah; Arjuna, Arjuna (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to explore the implementation of a mastery learning approach in enhancing verse comprehension in Al-Qur'an Hadith subjects at MA Hamasatul Muslimin Indonesia. Unlike conventional learning that emphasizes memorization, this study examines a systematic approach that prioritizes deep understanding of verse meanings before proceeding to subsequent materials. The research method employs a qualitative approach with a case study design, involving direct observation, in-depth interviews, and documentation. Data analysis utilizes Miles and Huberman's interactive analysis model with triangulation to ensure data validity.The research findings show that mastery learning implementation is conducted through orientation and presentation stages, structured practice in the form of muhadharah, guided practice with teacher assistance and peer tutoring, as well as independent practice through basic competency examinations. This approach creates learning that is not limited by space and time, positioning teachers as facilitators who encourage students' critical and reflective thinking. The findings indicate that the mastery learning approach is effective in developing contextual and applicative understanding of verse meanings, integrating cognitive, affective, and psychomotor dimensions holistically. This research contributes to the development of understanding-based learning practices in Islamic religious education and can serve as a reference for developing innovative learning strategies in Islamic educational institutions